A Pilot Study for Building Student Metacognitive Skills and Self-Perception in a Food Microbiology Lecture Course - Daly, Sarah E.; Gibney, Patrick A.; Snyder, Abigail B. (Teaching and Learning Inquiry, 2025)
Metacognition, or the monitoring of one’s own learning, is an underutilized tool in STEM education. Previous research suggests instructional strategies that attempt to improve student metacognitive skills could increase student resilience and retention in STEM classes. This pilot initiative aimed to improve student metacognitive skills and self-perception. To do so, metacognitive-based instructional strategies were added to the curriculum of a food microbiology lecture course. These instructional strategies encouraged students to build their metacognitive skills within a supportive classroom community. Student metacognitive skills, self-perception, and learning strategies were assessed throughout the semester. By the end of the semester, over a third of students reported using at least three higher-order learning strategies. Additionally, there were some significant changes in students’ sense of belonging and self-efficacy, with an overall positive improvement compared to their previous science lectures. This study found that metacognitive-based instructional strategies can be an important tool for improving students’ experiences in a food microbiology class.